Transforming invasive weeds into environmental solutions: Community-based biochar production from taberau (Phragmites australis) in Central Kalimantan - Abudarin Abudarin; I Nyoman Sudyana; Retno Agnestisia; Akhmad Damsyik; Siti Unvaresi Misonia Beladona; Alfalita Chendy Sarungu; Johan Yahya (Community Empowerment, 2026)
The Taberau plant (Phragmites australis) grows abundantly across the peat swamps of Central Kalimantan, particularly in Tanjung Sangalang Village. Despite its high biomass potential, it is widely dismissed as an invasive weed and remains underutilized. This community service program aims to empower local farmer groups by introducing a simple, local wisdom-integrated pyrolysis method to convert Taberau into multifunctional biochar. The program was executed through a comprehensive framework including local coordination, site surveys, Focus Group Discussions (FGD), simple reactor fabrication, hands-on demonstrations, and empirical evaluations. The production trials demonstrated that 20 kg of raw Taberau biomass yielded 5 kg of biochar, achieving an efficiency rate of approximately 25%. The training workshop, which engaged 40 local farmers, significantly elevated participants' technical comprehension, as evidenced by post-test scores exceeding 90% across all pedagogical indicators. Furthermore, 85% of respondents reported a substantial increase in environmental literacy, and 87.5% validated the tangible socio-economic benefits of the program. Ultimately, this initiative serves as a highly replicable model for circular economy practices in regions facing similar biomass management challenges.